Breakthroughs in biosciences and the question of morality: interactions between ethics and bioscience practices - Hashi, Abdurezak Abdulahi (Springer Singapore, 2016)
In the last four decades, scientific discoveries in the field of biosciences exhibited a progress that is remarkably ascending and covers issues which were traditionally not in the domains of ordinary medical science, including stem cell research, tissue engineering, surrogate motherhood, artificial insemination and test-tube babies as well as the mass scale production of genetically modified food. Nevertheless, as recent scientific breakthroughs involve critical issues related to human biology and health sciences, as well as to the sustainability of the natural environment, the place of moral values in modern breakthroughs and practices of biosciences emerge as matters of concern among scientists and scholars of ethics. One of the primary questions of this concern is related to whether or not scientific progress ought to be guided by what man ought to do, rather than what man can do. Similar issues are raised about the relationship between the applications of scientific discoveries and moral values. This research uses an analytical method and aims to present a comparative account of the bioethical discussions on the interactions between moral values and scientific discoveries in the field of bioscience.